Discrepancies Between Biopsy Gleason Score and Radical Prostatectomy Specimen Gleason Score: An Iranian Experience - Dolatkhah, Shahaboddin; Mirtalebi, Maryam; Daneshpajouhnejad, Parnaz; Barahimi, Ahmadreza; Mazdak, Hamid; Izadpanahi, Mohammad Hossein; Mohammadi, Mehrdad; Taheri, Diana (Urology Journal, 2019)
Purpose: Considering the importance of treatment decisions for prostate cancer (PCa) and the utility of Gleason scoring system (GS) in this field, we aimed to assess the percent of agreement and disagreement between needle biopsy (NB) Gleason score and radical prostatectomy (RP) specimen Gleason score. Materials and Methods: In this retrospective study, consecutive patients with PCa, who underwent NB and subsequently RP were enrolled. GS of both NB and RP specimens were recorded for each patient. Patients were classified according to the GS as low-grade (? 3+3), intermediate-grade (3+4 and 4+3), and high-grade (GS?8-10). The levels of agreement and discrepancy of NB GS was compared to its corresponding RP GS using Kappa coefficient of agreement. Over-grading and under-grading of NB GS were also determined. Result: A total of 100 embedded RP and corresponding NB were analyzed. The rate of discrepancy for group and individual scoring of GS was 41% and 56%, respectively. The rate of under and over-grading was 34% and 7%, respectively. Kappa value for group and individual scoring was .443 (95%CI: .313 - .573) and .411 (95%CI: .291 - .531), respectively. Conclusion: The findings of our study indicate that though the agreement between NB GS and RP GS are fair to moderate, but the feature of discrepancy, i.e. under-grading in low and intermediate grades and over-grading in high grades of NB GS, could help us in making more appropriate clinical decision especially considering other biochemical and pathological factors such as the level of PSA or peri-neural invasion.